The Association Between Diabetes and Olfactory Function in Adults. (8th November 2017) - Chan, Jason Ying Kuen; García-Esquinas, Esther; Ko, Owen H; Tong, Michael C F; Lin, Sandra Y
Abstract: Diabetes is a significant chronic disease that in limited studies has been linked with olfactory dysfunction. We investigated the cross-sectional association between diabetes and olfactory dysfunction in 3151 adults aged ≥40 years who participated in US National Health and Nutrition Examination Survey 2013–2014 with information on olfactory dysfunction and diabetes. Diabetes was defined from fasting serum glucose ≥126 mg/dL, oral glucose tolerance test ≥200 mg/dL, HbA1c levels ≥6.5%, physician-diagnosed diabetes, or current use of oral hypoglycemic agents and/or insulin. Self-reported olfactory dysfunction was defined as a positive answer to any of the following questions: 1) "Have you had problem with smell in the past 12 months?"; 2) "Have you had a change in the ability to smell since age 25?", or 3) "Do you have phantom smells?". Participants were considered to have severe hyposmia or anosmia if they had <5 correct answers in the 8-item pocket smell test. Analyses were adjusted for the main confounders, including olfactory dysfunction risk factors. Compared to non-diabetics, diabetics under insulin treatment showed a higher prevalence of phantom odors [OR(95% CI): 2.42 (1.16; 5.06)] and a non-significant higher prevalence of severe hyposmia/anosmia [OR(95% CI): 1.57 (0.89; 2.78)]. Amongst diabetics, there was a significant trend to severe hyposmia/anosmia for those on more aggressive treatments [OR (95% CI) including oral and insulin treatment compared to those who reported no use of drug treatment, respectively: 1.33 (0.60; 2.96) and 2.86 (1.28; 6.40); P trend 0.01]. No association was observed between diabetes duration and prevalence of olfactory dysfunction.